Aflatoxin contamination of maize flour in Kenya: Results from multi-city, multi-round surveillance - Vivian Hoffmann; Boaz Ndisio; Allan Barasa; Sheila Okoth; Mike Murphy (PLoS ONE, 2025)
Foodborne illness is a major source of the global burden of disease, but public monitoring of hazards in food systems is overwhelmingly focused on the formal sector in high income countries. We contribute to the development of an evidence base on food safety risk in low-income and informal settings by monitoring aflatoxin prevalence in maize flour in Kenya. Aflatoxin is a contaminant which causes liver cancer and has been linked to childhood stunting. We carry out systematic monitoring of formally and informally processed maize flour from a range of retail vendors across ten urban sites in Kenya and analyze aflatoxin levels in commercial samples. Samples were obtained every two months from February-December 2021 and 1255 samples in total were analyzed. Almost all samples (97%) showed detectable levels of aflatoxin, with 16% of tested samples exceeding the national regulatory limit of 10 ppb. Mean contamination levels are significantly higher (p < 0.001) in informal market samples (9.9 ppb) than in packaged flour in the formal sector (4.9 ppb). We find important seasonal variation in aflatoxin levels, which are highest in our June sample and lowest in December, which we attribute to variation in sourcing of maize grain. Our results demonstrate the need for policy interventions to reduce aflatoxin exposure in Kenya and demonstrate the utility of coordinated monitoring efforts to track levels of food safety risk in low-income settings.